Construction of Protein Probe with a His‐tag and an Electron‐transfer Peptide for a Target Protein Sensing. Issue 4 (23rd November 2020) - Sugawara, Kazuharu; Ishizaki, Sora; Kikuchi, Soya; Kuramitz, Hideki; Kadoya, Toshihiko
Abstract: A protein probe with an electron‐transfer peptide and a His‐tag was designed to electrochemically sense a target protein. We selected tyrosine‐rich (Y4 C) and tryptophan‐rich (W4 C) peptides for use as electron‐transfer agents. The peak for oxidation was based on the oxidations of the phenolic hydroxy groups in Y4 C and on the indole rings in W4 C. Asialofetuin (ASF) with galactose residues was the protein probe, and a galactose recognition protein, soybean agglutinin (SBA), was the target protein. A protein probe composed of an amino acid and carbohydrate residue was expected to be biocompatible. When voltammetric measurements were performed using a glassy carbon electrode, the oxidation peaks of H6 Y4 C and ASF‐H6 Y4 C appeared at the same potential. The peak current of ASF‐H6 Y4 C was 4‐fold that of H6 Y4 C because of the stronger adsorption of ASF‐H6 Y4 C onto the electrode. The electrode response of ASF‐H6 Y4 C with SBA was half that of ASF‐H6 Y4 C alone. By contrast, the peak current of ASF‐Y4 CH6 was higher than that of ASF‐H6 Y4 C, which was the result of a greater degree of contact between the Y4 C moieties and an electrode. On the other hand, the voltammetric behaviors of ASF with W4 C and a His‐tag were similar to those with Y4 C and a His‐tag. The sensitivity of SBA using ASF‐Y4 CH6 was at the 10 −13 M level. To confirm the function of the sensing system, measurements were performed in human serum with SBA and ASF‐Y4 CH6 . When SBA was added, the serum had a concentration that ranged between 5.0×10 −13 and 4.0×10 −12 M, and the amount of SBA that could be recovered ranged from 97 to 101%. Consequently, this system could be applied to the detection of SBA in serum. Abstract :